Engaging elite support for the poorest? BRAC`s experience with the ultra-poor program - Hossain, Naomi; Matin, Imran (Taylor and Francis, 2022)
This article was published in The Development in Practice [©2007 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/09614520701336923 The Article's website is at: https://www.tandfonline.com/doi/abs/10.1080/09614520701336923